Mechanisms of Impaired Lung Development and Ciliation in Mannosidase-1-Alpha-2 (Man1a2) Mutants - Ningappa, Mylarappa; Adenuga, Morayooluwa; Ngo, Kim A.; Mohamed, Nada; Narayanan, Tejaswini; Prasadan, Krishna; Ashokkumar, Chethan; Das, Jishnu; Schmitt, Lori; Hartman, Hannah; Sehrawat, Anuradha; Salgado, Claudia M.; et al. (Frontiers in Physiology, 2021)
Ciliary defects cause heterogenous phenotypes related to mutation burden which lead to impaired development. A previously reported homozygous deletion in the Man1a2 gene causes lethal respiratory failure in newborn pups and decreased lung ciliation compared with wild type (WT) pups. The effects of heterozygous mutation, and the potential for rescue are not known. Purpose: We hypothesized that survival and lung ciliation a) would decrease progressively in Man1a2 +/- heterozygous and Man1a2 -/- null newborn pups compared with WT, and b) could be enhanced by gestational treatment with N-Acetyl-cysteine (NAC), an antioxidant. Methods: Man1a2 +/- adult mice were fed NAC or placebo from a week before breeding through gestation. Survival of newborn pups was monitored for 24 hours. Lungs, liver and tails were harvested for morphology, genotyping and transcriptional profiling. Results: Survival (p=0.0001, Kaplan-Meier) and percent lung ciliation (p=0.0001, ANOVA) measured by frequency of Arl13b+ respiratory epithelial cells decreased progressively, as hypothesized. Compared with placebo, gestational NAC treatment enhanced a) lung ciliation in pups with each genotype, b) survival in heterozygous pups (p=0.017) but not in WT or null pups. Whole transcriptome of lung but not liver demonstrated patterns of up- and down-regulated genes that were identical in living heterozygous and WT pups, and completely opposite to those in dead heterozygous and null pups. Systems biology analysis enabled reconstruction of protein interaction networks that yielded functionally relevant modules and their interactions. In these networks, the mutant Man1a2 enzyme contributes to abnormal synthesis of proteins essential for lung development. The associated unfolded protein, hypoxic and oxidative stress responses can be mitigated with NAC. Comparisons with the developing human fetal lung transcriptome show that NAC likely restores normal vascular and epithelial tube morphogenesis in Man1a2 mutant mice. Conclusions: Survival and lung ciliation in the Man1a2 mutant mouse, and its improvement with N-Acetyl cysteine is genotype-dependent. NAC-mediated rescue depends on the central role for oxidative and hypoxic stress in regulating ciliary function and organogenesis during development